|
| 1 | +------------------------------------------------------------------------ |
| 2 | +-- The Agda standard library |
| 3 | +-- |
| 4 | +-- Some basic properties of Quasigroup |
| 5 | +------------------------------------------------------------------------ |
| 6 | + |
| 7 | +{-# OPTIONS --without-K --safe #-} |
| 8 | + |
| 9 | +open import Algebra.Bundles using (MiddleBolLoop) |
| 10 | + |
| 11 | +module Algebra.Properties.MiddleBolLoop {m₁ m₂} (M : MiddleBolLoop m₁ m₂) where |
| 12 | + |
| 13 | +open MiddleBolLoop M |
| 14 | +open import Algebra.Definitions _≈_ |
| 15 | +open import Relation.Binary.Reasoning.Setoid setoid |
| 16 | +open import Data.Product |
| 17 | +import Algebra.Properties.Loop as LoopProperties |
| 18 | +open LoopProperties loop public |
| 19 | + |
| 20 | +xyx\\x≈y\\x : ∀ x y → x ∙ ((y ∙ x) \\ x) ≈ y \\ x |
| 21 | +xyx\\x≈y\\x x y = begin |
| 22 | + x ∙ ((y ∙ x) \\ x) ≈⟨ middleBol x y x ⟩ |
| 23 | + (x // x) ∙ (y \\ x) ≈⟨ ∙-congʳ (x//x≈ε x) ⟩ |
| 24 | + ε ∙ (y \\ x) ≈⟨ identityˡ ((y \\ x)) ⟩ |
| 25 | + y \\ x ∎ |
| 26 | + |
| 27 | +xxz\\x≈x//z : ∀ x z → x ∙ ((x ∙ z) \\ x) ≈ x // z |
| 28 | +xxz\\x≈x//z x z = begin |
| 29 | + x ∙ ((x ∙ z) \\ x) ≈⟨ middleBol x x z ⟩ |
| 30 | + (x // z) ∙ (x \\ x) ≈⟨ ∙-congˡ (x\\x≈ε x) ⟩ |
| 31 | + (x // z) ∙ ε ≈⟨ identityʳ ((x // z)) ⟩ |
| 32 | + x // z ∎ |
| 33 | + |
| 34 | +xz\\x≈x//zx : ∀ x z → x ∙ (z \\ x) ≈ (x // z) ∙ x |
| 35 | +xz\\x≈x//zx x z = begin |
| 36 | + x ∙ (z \\ x) ≈⟨ ∙-congˡ (\\-congʳ( sym (identityˡ z))) ⟩ |
| 37 | + x ∙ ((ε ∙ z) \\ x) ≈⟨ middleBol x ε z ⟩ |
| 38 | + x // z ∙ (ε \\ x) ≈⟨ ∙-congˡ (ε\\x≈x x) ⟩ |
| 39 | + x // z ∙ x ∎ |
| 40 | + |
| 41 | +x//yzx≈x//zy\\x : ∀ x y z → (x // (y ∙ z)) ∙ x ≈ (x // z) ∙ (y \\ x) |
| 42 | +x//yzx≈x//zy\\x x y z = begin |
| 43 | + (x // (y ∙ z)) ∙ x ≈⟨ sym (xz\\x≈x//zx x ((y ∙ z))) ⟩ |
| 44 | + x ∙ ((y ∙ z) \\ x) ≈⟨ middleBol x y z ⟩ |
| 45 | + (x // z) ∙ (y \\ x) ∎ |
| 46 | + |
| 47 | +x//yxx≈y\\x : ∀ x y → (x // (y ∙ x)) ∙ x ≈ y \\ x |
| 48 | +x//yxx≈y\\x x y = begin |
| 49 | + (x // (y ∙ x)) ∙ x ≈⟨ x//yzx≈x//zy\\x x y x ⟩ |
| 50 | + (x // x) ∙ (y \\ x) ≈⟨ ∙-congʳ (x//x≈ε x) ⟩ |
| 51 | + ε ∙ (y \\ x) ≈⟨ identityˡ ((y \\ x)) ⟩ |
| 52 | + y \\ x ∎ |
| 53 | + |
| 54 | +x//xzx≈x//z : ∀ x z → (x // (x ∙ z)) ∙ x ≈ x // z |
| 55 | +x//xzx≈x//z x z = begin |
| 56 | + (x // (x ∙ z)) ∙ x ≈⟨ x//yzx≈x//zy\\x x x z ⟩ |
| 57 | + (x // z) ∙ (x \\ x) ≈⟨ ∙-congˡ (x\\x≈ε x) ⟩ |
| 58 | + (x // z) ∙ ε ≈⟨ identityʳ (x // z) ⟩ |
| 59 | + x // z ∎ |
0 commit comments